Integrating Behaviorist–Structuralist and Cognitive–Transformative Approaches in Arabic Language Learning - Muhamad Fuad Hasim; Hisbullah Huda; M. Baihaqi; Nelly Sakinah; M. Hudzaifah (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study examined the implementation of an approach integrating behaviorist–structuralist theory and cognitive–transformative generative principles in Arabic language instruction for seventh-grade students at MTs Miftahul Afkar, Kediri, Indonesia. Using a qualitative case study design, data were collected through classroom observations, in-depth interviews with the Arabic language teacher, and document analysis conducted from February 3 to February 28, 2025. The findings show that the behaviorist–structuralist approach effectively supports habit formation and structural accuracy, while cognitive–transformative generative principles enhance meaningful understanding and students’ ability to independently produce varied language forms. The study concludes that integrating these approaches results in systematic, meaningful, and transformative Arabic language learning and highlights the importance of developmentally sequenced instruction in madrasah education.